2004
DOI: 10.1590/s1415-47572004000100007
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic mRNA expression and plasma levels of insulin-like growth factor-I (IGF-I) in broiler chickens selected for different growth rates

Abstract: The hepatic expression and plasma concentrations of IGF-I were investigated in three broiler chicken strains selected for different growth rates (HP-Hubbard-Pettersen, a fast growing strain; NN-Naked-neck, a strain with an intermediate growth rate and a heterozygous genotype, and C-Caipira, a slow growing crossbred strain). The chickens were studied at 1, 21 and 42 days of age and had free access to food throughout the study. Hepatic IGF-I mRNA expression was assessed by dot blot analysis using a randomly labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
12
2
Order By: Relevance
“…; Giachetto et al . ). Our results, in great tits, show somewhat different pattern to that described in chickens.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Giachetto et al . ). Our results, in great tits, show somewhat different pattern to that described in chickens.…”
Section: Discussionmentioning
confidence: 97%
“…However, while this accumulated evidence shows that IGF‐1 is essential during growth and development, a direct correlation between the IGF‐1 and post‐natal body weight is often reported to be absent (Buyse & Decuypere ; Giachetto et al . ; Rahimi ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In domestic dogs, elevated GH (during early life) and IGF1 are associated with large dog breeds (44,45), and the IGF1 locus has been associated with variation influencing body size (46). Extensive work in domestic chickens and turkeys has found GH and IGF1 to be variably correlated with growth rate or to have an ability to further stimulate organismal or cellular growth (47)(48)(49)(50). In fish, fast-growing strains of rainbow trout have not been found to possess elevated plasma or pituitary GH or plasma IGF1 (51), and fast-growing Atlantic salmon showed no change in IGF1 but pituitary and plasma GH were elevated when examined across stages (52).…”
Section: Discussionmentioning
confidence: 99%
“…Lines of chickens selected for high or low growth rates were respectively associated with high and low circulating IGF-1 levels (17). In contrast, Giachetto et al (18) reported that hepatic IGF-1 mRNA and plasma IGF-1 levels were similar for chickens with different growth rates. For the Virginia Tech growth selected lines, the concentration of plasma GH is less and IGF-1 is greater in HWS than LWS chickens (19).…”
mentioning
confidence: 98%